1998
DOI: 10.1099/0022-1317-79-12-3111
|View full text |Cite
|
Sign up to set email alerts
|

Sequences of ten circular ssDNA components associated with the milk vetch dwarf virus genome.

Abstract: Milk vetch dwarf virus (MDV) is a member of the proposed genus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 45 publications
1
56
0
Order By: Relevance
“…DNA 5 has been shown to contain an LXCXE motif, and binding between DNA 5 products and retinoblastoma (Rb), demonstrated by yeast two-hybrid analysis, may be involved in host-cell cycle manipulation (82). In addition, more than one Rep-encoded component may be associated with virus infection in nanoviruses (22,29,30,39,63). Only one of these Rep genes, master Rep, can directly replicate non-self-replicable components, and remaining Rep-encoded components are considered to be satellite viruses (29,78,80).…”
mentioning
confidence: 99%
“…DNA 5 has been shown to contain an LXCXE motif, and binding between DNA 5 products and retinoblastoma (Rb), demonstrated by yeast two-hybrid analysis, may be involved in host-cell cycle manipulation (82). In addition, more than one Rep-encoded component may be associated with virus infection in nanoviruses (22,29,30,39,63). Only one of these Rep genes, master Rep, can directly replicate non-self-replicable components, and remaining Rep-encoded components are considered to be satellite viruses (29,78,80).…”
mentioning
confidence: 99%
“…No nanovirus component has been identified that contains an ORF similar to the internal ORF encoded by BBTV DNA-R. No function has been assigned to the ORFs located on the other nanovirus-specific components (DNA-U1 and DNA-U2). Multiple satellite DNAs, encoding non-essential Reps (otherwise known as para-Reps) have also been identified associated with nanoviruses, some of which shares homology with the satellite Rep encoding components of BBTV (Katul et al, 1995;Katul et al, 1998;Sano et al, 1998). …”
Section: Genus Nanovirusmentioning
confidence: 99%
“…Their multipartite genome consists of at least six to eight circular individually encapsidated ssDNA molecules of ca. 1 kb, with one virion sense open reading frame (ORF) each (5,7,23,35). Nanovirus DNA components and their respective encoded proteins of known function comprise DNA-R encoding the master Rep (M-Rep) protein (39), DNA-S encoding the capsid protein (43), DNA-C encoding the cell cycle link protein Clink (4), DNA-M encoding a movement protein, and DNA-N encoding a nuclear shuttle protein (42).…”
mentioning
confidence: 99%